MENUMBUHKAN SEMANGAT WIRAUSAHA MELALUI IDE KREATIF ECOBRICK DALAM MENJAGA KESEHATAN LINGKUNGAN DI SMA NEGERI 8 KOTA SERANG - Goni, Ahmad; Susanto, Denies (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
This Community Service Program (PKM) aims to increase environmental awareness and entrepreneurial spirit of students of SMAN 8 Serang City through the utilization of school waste such as plastic for use. The methods used include socialization of the impact of waste, development of economically valuable products, and entrepreneurship training. The results show an increase in participants' understanding of waste utilization. Based on the school's environmental concern, a group of students who care about waste was created who are committed to the cleanliness and health of the school environment and work together with the Serang City Waste Bank and the Environmental Service. This program has succeeded in providing environmental education through entrepreneurship, creating ideas that are useful for waste management while opening up creative economic opportunities